The relationship between dental anxiety and oral health-related quality of life in patients with periodontitis - Padilla Fonseca, Nicole (2024)
Abstract: Objectives: This study aimed to (1) investigate whether dental anxiety (DA) and oral health-related quality of life (OHRQoL) differed between patients diagnosed with periodontitis and individuals with periodontal health, (2) examine associations and correlations between these pa-tient-reported measures, and (3) analyze demographic and clinical parameters. Methods: Nine-ty-six patients diagnosed with periodontitis and age- and sex-matched periodontally healthy con-trols were included. Participants’ demographic characteristics, smoking status, current dental pain, dental pain during the last month, the Modified Corah’s Scale (MDAS), and the Oral Health Impact Profile (OHIP-14) were determined. Results: The mean age of participants was 48.51 years ± 11.41. Patients with periodontitis experienced higher pain in the last month compared to controls (p = 0.003). Patients with periodontitis exhibited significantly higher MDAS total and sub-scores (p < 0.001). Compared to controls, the periodontitis group indicated extreme DA (1.04% vs. 7.79%, p = 0.034). Patients with periodontitis feared having a foreign object in the mouth compared to controls (p = 0.004). The periodontitis group exhibited worse OHIP-14 global and sub-scores (all Ps < 0.001). Positive associations and correlations of MDAS total and sub-scores with OHIP-14 global and domain scores were found for the periodontitis group, but not for controls. Patients with periodontitis who reported “moderate and extreme anxiety” had poorer OHRQoL compared to controls (p = 0.001). The minimal importance difference for this finding indicates a large effect size and a moderate standardized response mean between groups. Conclusions: Patients with per-iodontitis had higher levels of DA and worse OHRQoL compared to controls. Our study highlights the importance of providing a comprehensive approach, including psychosocial well-being, when diagnosing and treating periodontal disease.